Numerical Wordplay in Digital Communication: A Corpus Linguistic Study on Cyber-pragmatics - Kunjana Rahardi; Wahyudi Rahmat (Jurusan Tadris Bahasa Indonesia, 2025)
This research aims to elucidate the pragmatic significance of employing numerical wordplay with humorous undertones from a cyber-text semio-pragmatics perspective. Social media serves as the primary data source, with textual content featuring instances of numerical wordplay with comedic elements constituting the substantive data. Data collection involved reading and note-taking techniques, followed by identification, selection, classification, and typification to distinguish between suitable and unsuitable data for analysis. Triangulation was employed to validate the data, involving both experts in the field and relevant theoretical frameworks. Contextual analysis was utilized as the analytical method to uncover the pragmatic meanings embedded within the use of numerical wordplay. The findings reveal various pragmatic functions, including concealing speech intent, maintaining secrecy, easing speech delivery, playful engagement, manipulation of speech intent, and inviting humor with speech partners. This research contributes theoretically to the advancement of pragmatics and cyber-pragmatics as interdisciplinary fields within linguistics, particularly in the realm of digital communication. Furthermore, it offers practical implications for fostering further research in pragmatics, especially in the emerging field of cyber-pragmatics, which warrants further exploration and scholarly attention. Permainan Kata Numerik dalam Komunikasi Digital: Sebuah Studi Linguistik Korpus tentang Pragmatik SiberPenelitian ini bertujuan untuk menjelaskan signifikansi pragmatis dari penggunaan permainan kata numerik dengan nada humor dari perspektif semio-pragmatik teks siber. Media sosial berfungsi sebagai sumber data utama, dengan konten tekstual yang menampilkan contoh permainan kata numerik dengan elemen komedi yang merupakan data substantif. Pengumpulan data melibatkan teknik membaca dan mencatat, diikuti oleh identifikasi, pemilihan, klasifikasi, dan tipifikasi untuk membedakan antara data yang sesuai dan tidak sesuai untuk analisis. Triangulasi digunakan untuk memvalidasi data, melibatkan para ahli di lapangan dan kerangka teoritis yang relevan. Analisis kontekstual digunakan sebagai metode analisis untuk mengungkap makna pragmatis yang tertanam dalam penggunaan permainan kata numerik. Temuan tersebut mengungkapkan berbagai fungsi pragmatis, termasuk menyembunyikan maksud ujaran, menjaga kerahasiaan, memudahkan penyampaian ujaran, keterlibatan yang menyenangkan, manipulasi maksud ujaran, dan mengundang humor dengan mitra tutur. Penelitian ini berkontribusi secara teoritis terhadap kemajuan pragmatik dan pragmatik siber sebagai bidang interdisipliner dalam linguistik, khususnya dalam bidang komunikasi digital. Lebih jauh, penelitian ini menawarkan implikasi praktis untuk mendorong penelitian lebih lanjut dalam pragmatik, khususnya dalam bidang cyber-pragmatik yang sedang berkembang, yang memerlukan eksplorasi lebih lanjut dan perhatian ilmiah.